Anxiety Levels Related to Flood Exposure in Disaster Victims - Suniarti Sunny; Sri Setyowati (Universitas Muhammadiyah Semarang, 2020)
One of the impacts caused by natural disasters is the increased level of anxiety in the community which, if left unchecked, might disrupt their life cycle. For example, the flood disaster that occurred in Imogiri, Yogyakarta in March 2019 is thought to have increased anxiety in the affected community so that handling efforts need to be done. This study aims to determine the correlation between the level of anxiety and the flood disaster that occurred in Imogiri. The population of respondents in this study were flood victims in Imogiri District. Samples were taken by 68 respondents with a non-probability sampling technique, namely accidental sampling. Data collection has been carried out through a survey using a questionnaire to 68 respondents spread across four villages in Imogiri. Data analysis was performed using the chi-square test. The results showed that there was a significant correlation (p <0.05; r = 0.584) between the level of anxiety and flood exposure in flood victims in Imogiri.